LEGAL AND METALINGUISTIC CONSCIOUSNESSES OF FUTURE POLICEMEN - CКОРОФАТОВА, Анна (Comparative Legilinguistics, 2017)
In this article the notion of metalinguistic consciousness is defined as an area of a human being’s knowledge about the language, and professional linguistic consciousness is defined as psycholinguistic model that reconstructs the system of basic images of consciousness formed by professionally oriented means of language. It is the specific of future policemen’s linguistic consciousness that the central part of it must be legal consciousness. In the article the elements of legal consciousness in the structure of policemen’s linguistic personality are exposed on the basis of reconstructing concepts that present specific legal categories and notions: right and duties, law and legality, court, justice, crime, punishment and others. The method of associative experiment was used. As a result of the experiment it is possible to assert that the percent of terminological linguistic units in the future policemen’s linguistic consciousness (61,5%) shows that professional personality in the third-year students is not formed enough. Nevertheless, there are professionally marked cognitive structures in future policemen’s consciousness. In reconstructed associative fields become actual the connections between legal concepts and basic signs of legal society (24,0%), generalizing and specifying legal concepts (11,0% and 3,8%), law applying activity (13,7%), authenticness of official language (3,8%), legal acts (3,0%), scientific sphere (2,2%). However emotional and evaluating components of investigated concepts for students’ professional linguistic consciousness are also appeared actual (38,5%).